2018
DOI: 10.1002/joc.5437
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the active typhoon season in 2016 following a strong El Niño with a comparison to 1998

Abstract: This article analysed two typhoon seasons (1998 and 2016) over the western North Pacific (WNP) with similar preceding background conditions of the tropical Pacific sea surface temperature (SST). Following the strong El Niño event in the preceding winter, the typhoon season was inactive in 1998 while active in 2016. Compared with 1998, the monsoon trough (MT) in 2016 shifted more eastwards, leading to an increase of the mid‐level water vapour, lower‐tropospheric relative vorticity and upper‐tropospheric diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…The El Niño events in the winters of 1997/98 and 2015/16 as two strongest events since observational records, their intensities were higher than twice the standard deviation of the Niño-3.4 index, which attracted wide attention from the academic community (C. Gao et al 2018;Huangfu et al 2018). Using NOAA and Hadley sea surface temperature data, we analyzed the Niño-3.4 (58S-58N, 1708-1208W) and Niño-3 (58S-58N, 1508-908W) indices and found that the two El Niño events had similar intensities and decaying processes (figure not shown), which was consistent with the results of previous studies (C. Huangfu et al 2018). Gao et al (2018) analyzed the early summer (May-July) precipitation anomaly pattern in the pan-Asian monsoon region and its physical mechanism during a strong El Niño decaying year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The El Niño events in the winters of 1997/98 and 2015/16 as two strongest events since observational records, their intensities were higher than twice the standard deviation of the Niño-3.4 index, which attracted wide attention from the academic community (C. Gao et al 2018;Huangfu et al 2018). Using NOAA and Hadley sea surface temperature data, we analyzed the Niño-3.4 (58S-58N, 1708-1208W) and Niño-3 (58S-58N, 1508-908W) indices and found that the two El Niño events had similar intensities and decaying processes (figure not shown), which was consistent with the results of previous studies (C. Huangfu et al 2018). Gao et al (2018) analyzed the early summer (May-July) precipitation anomaly pattern in the pan-Asian monsoon region and its physical mechanism during a strong El Niño decaying year.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, during the El Niño decaying summer of August 2016, the number of TCs increased and they generated in the east, which is not consistent with the findings of previous research. Huangfu et al (2018) compared the differences of TC activities between 1998 and 2016 during two super-El Niño decaying summers. They found that the active typhoon in 2016 was attributed to the eastward extension of the monsoon trough (MT), more active tropical depression wave activities, and the slow developing process of La Niña-like SST during this year.…”
Section: B Discussionmentioning
confidence: 99%
“…The evolutionary characteristics of the El Niño events are also an issue worthy of study. In previous studies, the phase in which the sea surface temperature anomalies (SSTA) gradually weakens after the maturity of El Niño is usually defined as the decaying phase of the El Niño event (Lin and Li 2008, Jiang et al 2017, Huangfu et al 2018. Different rates at which El Niño events decay modulate the atmospheric circulation and oceanic environment differently in the surrounding areas (Pillai and Chowdary 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The synoptic‐scale wave train is characterized by northwest–southeast‐oriented alternating cyclonic and anticyclonic disturbances, with a typical wavelength of 2,500–3,000 km and a period of less than 10 days (Chang, Chen, Harr, & Carr, 1996; Feng et al, 2016; Fu, Li, Peng, & Weng, 2007; Fukutomi et al, 2016; Huang & Huang, 2011; Lau & Lau, 1990, 1992; Li, 2006; Tam & Li, 2006; Yuan, Li, & Wang, 2015; Zhao, Jiang, & Wu, 2016a). The synoptic‐scale wave train has been extensively studied for its role in extremely heavy rainfall events (Wu, Fukutomi, & Matsumoto, 2011; Yokoi & Matsumoto, 2008), seeding tropical cyclone (TC) genesis (Cao, Chen, & Chen, 2013; Dickinson & Molinari, 2002; Fu et al, 2007; Huangfu, Chen, Wang, & Huang, 2018c; Huangfu, Huang, Chen, & Feng, 2018d; Huangfu, Chen, Huang, & Feng, 2019; Li, Fu, Ge, Wang, & Peng, 2003; Xu, Li, & Peng, 2014; Yuan et al, 2015; Zhao et al, 2019; Zhou & Wang, 2007), and interactions with low‐frequency activities, for example, intra‐seasonal oscillations (ISOs; Sobel & Maloney, 2000; Aiyyer & Molinari, 2003; Maloney & Dickinson, 2003; Straub & Kiladis, 2003; Zhou & Li, 2010; Hsu, Li, & Tsou, 2011; Li, 2014; Zhao et al, 2016a; Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%